Diagnosis and management of infectious pleural effusion. - Rahman, N; Chapman, S; Davies, R (2006)
Pleural infection remains a common illness, with a high morbidity and mortality. The development of frank empyema from a simple exudative pleural effusion is a result of biochemical changes within the pleural space in response to bacterial invasion. These changes can be used in the diagnosis of pleural infection and used to predict which patients will require intercostal drainage for resolution of infection. Recent large trials in empyema have further advanced our knowledge of microbiologic patterns, informing important decisions about empiric antibacterial therapy. Diagnosis of pleural infection relies on high clinical suspicion in association with clinical features, radiology, and pleural fluid characteristics. Treatment of pleural infection is based upon accurate and often empiric choice of antibacterial agents, intercostal drainage in certain contexts, and appropriate surgical referral. Intrapleural thrombolytic therapy is not currently recommended for the treatment of pleural infection, on the basis of evidence from the largest randomized trial in empyema to date.